The Role of Cardiovascular Risk Factors and Risk Scoring Systems in Predicting Coronary Atherosclerosis - Gormel,Suat (2021)
Abstract Background Comparative data on the performance of cardiovascular risk scoring systems (CRSSs) in patients with severe coronary artery disease (CAD) are lacking. Objectives To compare different CRSSs regarding their ability to discriminate patients with severe CAD. Method A total of 414 patients (297 men; 61.3±12.3 years of age) undergoing coronary angiography were enrolled and evaluated for major risk factors. Cardiovascular risk and risk category were defined for each patient using the Framingham, Systemic Coronary Risk Evaluation (SCORE), and Pooled Cohort Risk Assessment Equation (PCRAE) tools. Severe CAD was defined as ≥ 50% stenosis in at least one major coronary artery and/or previous coronary stenting or coronary artery bypass grafting. A p < 0.05 was considered statistically significant. Results Severe CAD was identified in 271 (65.4%) patients. The ROC curves of the 3 CRSSs for predicting severe CAD were compared and showed no significant difference: the area under the ROC curve was 0.727, 0.694, and 0.717 for the Framingham, SCORE, and PCRAE tools, respectively (p > 0.05). However, when individual patients were classified as having low, intermediate, or high cardiovascular risk, the rate of patients in the high-risk group was significantly different between the PCRAE, Framingham, and SCORE tools (73.4%, 27.5%, and 37.9%, respectively; p < 0.001). Discussion PCRAE had higher positive and negative predictive values for detecting severe CAD in high-risk patients than the Framingham and SCORE tools. Conclusion We can speculate that currently used CRSSs are not sufficient, and new scoring systems are needed. In addition, other risk factors, such as serum creatinine, should be considered in future CRSSs. Int J Cardiovasc Sci. 2020; [online].ahead print, PP.0-0